Akibat hukum Berlakunya Undang-Undang Ibu Kota Negara terhadap Hak Ulayat di Kalimantan Timur - Aushofi Zuhrotul Ulya; Putri Kinanthi; Salsabilla Shofia; Veronica Cynthia Wibowo (Notaire, 2022)
AbstractIndonesia as a multicultural country has recognized the existence of indingenous people along with their right, which is Ulayat Right or the right to control, govern and take care of a specific land. With the enactment of State Capital Law on February 15th 2022, the capital city of Indonesia will be relocated from Jakarta to East Borneo. The relocation of Indonesia’s capital will potentially use Ulayat Land, the land that belongs to the indingenous people, and can cause conflicts within the society. Thus, this research intends to analyze the legal standing of Ulayat Right in East Borneo after the enactment of State Capital Law and legal protection for indingenous people that are impacted by the government through State Capital Law. This writing is a legal doctrinal research that uses statute approach and conceptual approach. The analysis shows that the process of relocating the state’s capital is categorized as land acquisition for public interest, regulated on Article 16 (3) of State Capital Law. Thus, the Government has the authority to acquire the land in question as long as they regard the impacted parties and their rights. The legal protection for those who are impacted by State Capital Law is by receiving compensation for the land and they could also submit an objection to the local District Court.Keywords: Indingenous People; Ulayat Right; State Capital Law; Land Acquisition; Public Interest. AbstrakIndonesia sebagai negara multikultural mengakui eksistensi masyarakat adat beserta hak yang dimilikinya, yaitu Hak Ulayat atau hak untuk menguasai, mengatur dan mengurus tanah. Dengan disahkannya UU IKN pada 15 Februari 2022, maka Ibu Kota Negara akan beralih dari Jakarta ke Kalimantan Timur. Proses pemindahan Ibu Kota Negara berpotensi untuk menggusur tanah adat sehingga dapat menimbulkan konflik di kalangan masyarakat adat. Oleh karena itu, penulisan ini membahas kedudukan Hak Ulayat Kalimantan Timur setelah adanya UU IKN dan bagaimana perlindungan hukum masyarakat adat atas penggunaan Hak Ulayat oleh pemerintah akibat UU IKN. Penelitian ini merupakan penelitian doktrinal hukum yang menggunakan pendekatan perundang-undangan dan konseptual. Hasil analisis penulis pembangunan Ibu Kota Negara dikategorikan sebagai pengadaan tanah untuk kepentingan umum sebagaimana diatur Pasal 16 Ayat (3) UU IKN. Sehingga, Tanah Ulayat dapat digunakan sebagai pembangunan Ibu Kota Negara dengan syarat Pemerintah harus tetap memperhatikan masyarakat adat yang terdampak akibat UU IKN tersebut. Perlindungan hukum yang diberikan berupa ganti kerugian atas tanah yang diserahkan dan keberatan apabila masyarakat adat menilai ganti kerugian yang diberikan tidak sesuai.Kata Kunci: Masyarakat Adat; Hak Ulayat; UU IKN; Pengadaan Tanah; Kepentingan Umum.